Characterization of Glucomannan Extracted from Fresh Porang Tubers Using Ethanol Technical Grade - Nurlela Nurlela; Nina Ariesta; Dwi Sutari Laksono; Edi Santosa; Tjahja Muhandri (Universitas Jenderal Soedirman, 2021)
Glucomannan is a polysaccharide consisting of β-1.4-linked D-mannose and D-glucose monomers, which have many benefits especially in the food and pharmaceutical industry. It has been widely reported that one of the main sources of glucomannan is porang tuber (Amorphophallus muelleri Blume). Generally, glucomannan extracted or purified from porang flour. However, the drying process causes other compounds than glucomannan stick strongly, resulting low levels of glucomannan. This study was to obtain glucomannan extract in an easy, effective, and inexpensive method, by direct extraction from fresh porang tubers using ethanol technical grade. We performed two extraction methods. The first is a fixed concentration method, the sample was repeatedly extracted using 50% ethanol (FC50) and 96% ethanol (FC96) 3 times, respectively. The second is a multilevel concentration method, the sample was repeatedly extracted using ethanol 60% (first step), 80% (second step), and 96% (third step), one replication each step. The highest glucomannan content (66.56%) was obtained by a multilevel concentration method. Moisture, lipid, protein, crude fiber, calcium oxalate level significantly reduce to 13.58%, 0.07%, 4.03%, 4.95%, 0.56% respectively. FTIR spectra confirmed the presence of functional groups (O-H, C=O, C-O, C-H), that compose the glucomannan compound. SEM image showed that the granules form of glucomannan were round and oval, began to change its phase from amorphous to crystalline, related to XRD data. The results showed that the direct extraction from fresh porang tuber using ethanol technical grade with a multilevel concentration method was an effective method to extract the glucomannan